2019
DOI: 10.1186/s40478-019-0798-z
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic downregulation of STAT6 increases HIF-1α expression via mTOR/S6K/S6, leading to enhanced hypoxic viability of glioma cells

Abstract: Multifunctional signal transducer and activator of transcription (STAT) proteins play important roles in cancer. Here, we have shown that STAT6 is epigenetically silenced in some cases of malignant glioblastoma, which facilitates cancer cell survival in a hypoxic microenvironment. This downregulation results from hypermethylation of CpG islands within the STAT6 promoter by DNA methyltransferases. STAT6 interacts with Rheb under hypoxia and inhibits mTOR/S6K/S6 signaling, in turn, inducing increased HIF-1α tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Cytokines IL-4 and IL-13. And also interacted with and immune cells (B and T cells, macrophages, dendritic cells, and innate lymphoid cells in brain tumors [17] . STAT6 signaling inactivation can occur via ubiquitination and proteasomal degradation, facilitating cancer cell survival in a hypoxic microenvironment [18] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokines IL-4 and IL-13. And also interacted with and immune cells (B and T cells, macrophages, dendritic cells, and innate lymphoid cells in brain tumors [17] . STAT6 signaling inactivation can occur via ubiquitination and proteasomal degradation, facilitating cancer cell survival in a hypoxic microenvironment [18] .…”
Section: Discussionmentioning
confidence: 99%
“…STAT6 signaling inactivation can occur via ubiquitination and proteasomal degradation, facilitating cancer cell survival in a hypoxic microenvironment [18] . STAT6 increases HIF-1α expression via mTOR/S6K/S6 [17,19] . Expression of stat6 in Cps is correlated to tumor invasion and recurrent tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, STAT6 is an important target protein of IL-4 that likely regulates the microenvironment of tumor cell growth, inhibits tumor invasion, and reduces tumor proliferation and differentiation (Rahaman et al, 2005 ; Hammond et al, 2018 ). Both in human glioma tissue and glioblastoma cells (U87MG and U373MG), Park et al ( 2019 ) found that CpG islands in the STAT6 promoter were hypermethylated by DNA methyltransferase which ultimately led to the down-regulated and even silenced expression of STAT6. Furthermore, under hypoxic conditions, the decrease of STAT6 could activate the mTOR signaling pathway, promote hypoxia-inducible factor-1 (HIF-1α) protein synthesis, and eventually enhance the viability and anti-apoptotic ability of tumor cells.…”
Section: Il-4 Glial Cells and Epilepsymentioning
confidence: 99%
“…Furthermore, under hypoxic conditions, the decrease of STAT6 could activate the mTOR signaling pathway, promote hypoxia-inducible factor-1 (HIF-1α) protein synthesis, and eventually enhance the viability and anti-apoptotic ability of tumor cells. Using DNA methyltransferase inhibitors, such as five-azacitidine and decitabine, to restore STAT6 expression in STAT6-silenced gliomas can increase tumor cell death, which would provide a new treatment (Park et al, 2019 ). Interestingly, in glioblastoma cells (U251, T98G, and A172), Rahaman et al found that IL-4 induced the abnormal activation of STAT3 in GBM cells, but not in normal human astrocytes.…”
Section: Il-4 Glial Cells and Epilepsymentioning
confidence: 99%
“…These cancer cell lines have acquired mutations and aberrant epigenetic marks that enable them to display malignancy. For example, the LN229 cell line was found to have mutations in p53 (Van Meir et al, 1994), deletions of p16 and p18 tumour suppressor genes (Wiedemeyer et al, 2008), and DNA methylations that epigenetically silence expression of tumour suppressor STAT6 (Park et al, 2019). There are other more somatic mutations and epigenetic alterations in these cell lines that will not be described here.…”
Section: Acly Overexpression Has No Role In Inducing Permanent Histone Acetylations To Regulate Expression Of Dna Damage Response Proteinmentioning
confidence: 99%